Three-dimensional Modeling of Tidal Hydrodynamics in the San Francisco Estuary - Edward S. Gross; Michael L. MacWilliams; Wim J. Kimmerer (San Francisco Estuary and Watershed Science, 2010)
Simulations of circulation in the San Francisco Estuary were performed with the three-dimensional TRIM3D hydrodynamic model using a generic length scale turbulence closure. The model was calibrated to reproduce observed tidal elevations, tidal currents, and salinity observations in the San Francisco Estuary using data collected during 1996-1998, a period of high and variable freshwater flow. It was then validated for 1994-1995, with emphasis on spring of 1994, a period of intensive data collection in the northern estuary. The model predicts tidal elevations and tidal currents accurately, and realistically predicts salinity at both the seasonal and tidal time scales. The model represents salt intrusion into the estuary accurately, and therefore accurately represents the salt balance. The model’s accuracy is adequate for its intended purposes of predicting salinity, analyzing gravitational circulation, and driving a particle-tracking model. Two applications were used to demonstrate the utility of the model. We estimated the components of the longitudinal salt flux and examined their dependence on flow conditions, and compared predicted salt intrusion with estimates from two empirical models.